Good Girls, Bad Ghouls - Chan, Chloe Xin Xu (2016)
"Good Girls, Bad Ghouls" is a feminist zine exploring Southeast Asian female mythical beings, with a strong focus on female spirit creatures of the Malay Archipelago. Research was conducted in various areas of study, including: the historical and cultural background in which the myths of these figures emerged, and feminist theory in areas such as psychoanalytic critique, body studies and anthropology. As female beings that share particular traits, these figures are reflections of perceptions towards women and issues that women face. By looking at these figures as gendered beings, the project aims to deconstruct and decode these spectral figures and the myths that surround them.